1985
DOI: 10.1002/mpo.2950130502
|View full text |Cite
|
Sign up to set email alerts
|

Response rate and survival in myeloma patients receiving prednisone alone

Abstract: Thirty-two evaluable good risk patients with multiple myeloma received a 70-day tapering course of prednisone beginning at a dose of 1.2 mg/kg/day. Forty-four percent of the patients demonstrated objective evidence of response to this treatment. Although the median time to disease progression for the prednisone-treated group was shorter than for patients randomized to receive prednisone with alkylating agents or who were treated with alkylating agent alone, the results from this trial indicate that prednisone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Prednisone as a single agent has also been shown to produce an objective response rate of 44% in a reanalysis of two myeloma treatment protocols. 17 The classic MP combination was born in 1969 when a trial of 183 patients with melphalan versus MP demonstrated a survival improvement by 6 months in MP arm. 18 Over the next 3 decades, multiple combination chemotherapies were compared with MP, yielding conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone as a single agent has also been shown to produce an objective response rate of 44% in a reanalysis of two myeloma treatment protocols. 17 The classic MP combination was born in 1969 when a trial of 183 patients with melphalan versus MP demonstrated a survival improvement by 6 months in MP arm. 18 Over the next 3 decades, multiple combination chemotherapies were compared with MP, yielding conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…37 In a reanalysis of 2 Cancer and Leukemia Group B myeloma treatment protocols, prednisone as a single agent produced a 44% objective response rate. 38 The classic regimen of melphalan plus prednisone (MP) was established in a randomized trial of 183 myeloma patients led by Alexanian et al, in which survival was 6 months longer with MP compared with melphalan alone. 39 Harley et al introduced the combination of carmustine, melphalan, cyclophosphamide, and prednisone in the treatment of multiple myeloma.…”
Section: Origins Of Alkylator and Corticosteroid-based Therapymentioning
confidence: 99%
“…It is well documented that glucocorticoids have antitumor activity in myeloma. [14][15][16][17][18] For patients either responding or showing stable disease following conventional chemotherapy, a single-arm study demonstrated that maintenance therapy with oral prednisone (50 mg 3 times per week) and interferon resulted in a long duration of remission and overall survival. 19 In a Southwest Oncology Group (SWOG) study, 89 patients responding to induction vincristine, doxorubicin, and dexamethasone (VAD) chemotherapy were randomized to receive maintenance therapy with either maintenance prednisone (50 mg 3 times per week with interferon or interferon alone).…”
Section: Introductionmentioning
confidence: 99%